Impact of obesity on the survival of patients with early‐stage squamous cell carcinoma of the oral tongue. Issue 7 (21st January 2014) - Iyengar, Neil M.; Kochhar, Amit; Morris, Patrick G.; Morris, Luc G.; Zhou, Xi K.; Ghossein, Ronald A.; Pino, Alejandro; Fury, Matthew G.; Pfister, David G.; Patel, Snehal G.; Boyle, Jay O.; Hudis, Clifford A.; et al.
Abstract : BACKGROUND: Although obesity increases risk and negatively affects survival for many malignancies, the prognostic implications in squamous cell carcinoma (SCC) of the oral tongue, a disease often associated with prediagnosis weight loss, are unknown. METHODS: Patients with T1‐T2 oral tongue SCC underwent curative‐intent resection in this single‐institution study. All patients underwent nutritional assessment prior to surgery. Body mass index (BMI) was calculated from measured height and weight and categorized as obese (≥ 30 kg/m 2 ), overweight (25‐29.9 kg/m 2 ), or normal (18.5‐24.9 kg/m 2 ). Clinical outcomes, including disease‐specific survival, recurrence‐free survival, and overall survival, were compared by BMI group using Cox regression. RESULTS: From 2000 to 2009, 155 patients (90 men, 65 women) of median age 57 years (range, 18‐86 years) were included. Baseline characteristics were similar by BMI group. Obesity was significantly associated with adverse disease‐specific survival compared with normal weight in univariable (hazard ratio [HR] = 2.65, 95% confidence interval [CI] = 1.07‐6.59; P = .04) and multivariable analyses (HR = 5.01; 95% CI = 1.69‐14.81; P = .004). A consistent association was seen between obesity and worse recurrence‐free survival (HR = 1.87; 95% CI = 0.90‐3.88) and between obesity and worse overall survival (HR = 2.03; 95% CI = 0.88‐4.65) though without reaching statistical significance ( P = .09 and P = .10, respectively) in multivariable analyses. CONCLUSIONS: In this retrospective study, obesity was an adverse independent prognostic variable. This association may not have been previously appreciated due to confounding by multiple factors including prediagnosis weight loss. Cancer 2014;120:983–991 . © 2013 American Cancer Society . Abstract : In patients with early tumor stage squamous cell carcinoma of the oral tongue, obesity was an independent predictor of worse disease‐specific survival in this retrospective study. This novel prognostic association may not have previously been recognized due to several confounding factors including prediagnosis weight loss.